Algorithms for the computation of moduli spaces for semiquasihomogeneous singularities - Bayer, Thomas (Revista Matemática Complutense, 2003)
We present algorithms and their implementation in the computer algebra system Singular 2.0 for the computation of equations for moduli spaces for semiquasihomogeneous singularities w.r.t. right equivalence. In addition, we describe the structure of the stabilizer group of Brieskorn-Pham singularities